Serum IL-23, IL-10, and TNF-α predict in-hospital mortality in COVID-19 patients - Smail, Shukur Wasman; Babaei, Esmaeil; Amin, Kawa; Abdulahad, Wayel H. (Frontiers in Immunology, 2023)
Objective: The hyperinflammatory response, caused by severe acute respiratory syndrome-2 (SARS-CoV-2), is the most common cause of death in patients with coronavirus disease 2019 (COVID-19). The etiopathogenesis of this illness is not fully understood. Macrophages appear to play a key part in COVID-19's pathogenic effects. Therefore, this study aims to examine serum inflammatory cytokines associated with the activation state of macrophages in COVID-19 patients and attempt to find accurate predictive markers for disease severity and mortality risk in hospital. Methods: 180 patients with COVID-19 and 90 healthy controls (HCs) participated in this study. Patients were divided into three different subgroups, mild (n=81), severe (n=60), and critical groups (n=39). Following admission to the hospital, all of the volunteers’ blood were collected in a gel tube, and IL(Interleukin)-10, IL-23, and chemokine ligand 3 (CCL3) were determined by ELISA. In parallel, myeloperoxidase (MPO) and C-reactive protein (CRP) were measured using colorimetric and electrochemiluminescence methods, respectively. Results: Compared to HCs, a significant increase in IL-23 and IL-10 levels was observed in serum samples of COVID-19 patients. Regarding CRP, significant increases were found in the severe and critical groups but not in the mild group compared to HCs. In addition, non-significant changes were found in serum MPO and CCL3 among the studied groups. CRP with IL-23 and IL-10 were shown to have a substantial correlation. Results showed that IL-10 alone or in combination with IL23 is strongly linked with non-survivors in COVID-19 patients. Finally, ROC curve results uncovered that a combination of IL-10 and IL-23 were excellent predictors for prognosing COVID-19. Conclusion: The elevations of IL-10 and IL-23 levels were seen in severe and critical cases of COVID-19 patients and their elevations were linked to the in-hospital mortality of the disease. A prediction model shows that the determination of these cytokines upon admission is important and should be done on COVID-19 patients as a way of evaluating the prognosis of the disease. COVID-19 Patients with high IL-10 and IL-23 on admission are more likely to experience a severe form of the disease; therefore, those patients should be cautionary monitored and treated.